Lymphoid V(D)J recombination: nucleotide insertion at signal joints as well as coding joints. - Lieber, M R (1988)
The coding regions of antigen receptor genes assembled by variable-diversity-joining region [V(D)J] recombination are known in many cases to have undergone deletions of several nucleotides and also to contain insertions of noncoded nucleotides at the recombined junction (the coding joint). By using extrachromosomal recombination substrates to transfect lymphoid cell lines, we show that the signal joint (the fusion of the corresponding recognition signal sequences) can also contain insertions; however, nucleotide loss from the signals is very rare. The frequency of nucleotide addition varies among pre-B-cell lines in a manner proportional to their content of terminal deoxynucleotidyltransferase. We also find frequent nucleotide additions (and deletions) at coding joints, but in this case there is no strong correlation with the level of terminal deoxynucleotidyltransferase activity. Inserts at both signal and coding joints are rich in G + C, consistent with the base utilization preference of this enzyme.